Using the Internet User’s Self-report Diagnostic Tool to Study Specific Characteristics of Internet-based Socialization Among Adolescents and Young Adults with Intellectual Disabilities - Татьяна И. Кузьмина (Российский психологический журнал, 2021)
Introduction. The study of specific characteristics of online socialization among adolescents and young adults with disabilities, especially intellectual disabilities, is a new and promising direction in special education that requires the development of methodological approaches and foundations for conducting research of this kind.